2021
DOI: 10.3390/su132212653
|View full text |Cite
|
Sign up to set email alerts
|

Towards Electric Price and Load Forecasting Using CNN-Based Ensembler in Smart Grid

Abstract: Medium-term electricity consumption and load forecasting in smart grids is an attractive topic of study, especially using innovative data analysis approaches for future energy consumption trends. Loss of electricity during generation and use is also a problem to be addressed. Both consumers and utilities can benefit from a predictive study of electricity demand and pricing. In this study, we used a new machine learning approach called AdaBoost to identify key features from an ISO-NE dataset that includes daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…In this article, the history of energy load and price information from several different new England cities is utilized. ISONE, which is utilized in this article [5], maintains the power load information. The vertical data, or columns, are referred to as "features."…”
Section: Proposed Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…In this article, the history of energy load and price information from several different new England cities is utilized. ISONE, which is utilized in this article [5], maintains the power load information. The vertical data, or columns, are referred to as "features."…”
Section: Proposed Methodologymentioning
confidence: 99%
“…There is a substantial amount of accurate data [4]. In the end-user, a good decision process minimizes power loss, lowers energy expenditures and lowers Peak Average Ratio (PAR) [5].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the original version of this algorithm is used by Aslam et al for electric price and load forecasting using CNN-based ensembler in smart grid. 32 They employed CHI algorithm to develop the efficacy of the classifier hyperparameters to modify the performance of them. Moreover, another work by Makhadmeh et al 33 modifies the CHI algorithm to deal with discrete optimization problems.…”
Section: Hismentioning
confidence: 99%
“…For instance, Li et al [15] forecasted electricity price based on a long shortterm memory (LSTM) neural network, using a test period of 4 weeks. Aslam et al [16] focused on the performance of a convolutional network (CNN) in medium-term electricity price forecasting, and showed that the CNN model performs well. Yang et al [17] built an innovative model based on a deep neural network (DNN) for electricity price forecasting, using a test dataset spanning a month.…”
Section: Introductionmentioning
confidence: 99%